2013
DOI: 10.1093/trstmh/trt112
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory treatment with thalidomide in experimental leptospirosis in Golden Syrian hamsters (Mesocricetus auratus)

Abstract: Thalidomide had minimal impact on survival in the late treatment of leptospirosis hamster model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…To explore the effect of LPS neutralization on severe leptospirosis, six-week-old male or female hamsters were inoculated intraperitoneally with 10 7 leptospires. Treatments were started immediately after detection of the first death regardless of the assigned group [19]. Group 1: saline control (400 μL/hamster, i.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the effect of LPS neutralization on severe leptospirosis, six-week-old male or female hamsters were inoculated intraperitoneally with 10 7 leptospires. Treatments were started immediately after detection of the first death regardless of the assigned group [19]. Group 1: saline control (400 μL/hamster, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Treatments were started immediately after detection of the first death regardless of the assigned group [19] . Group 1: saline control (400 μL/hamster, i.p.…”
Section: Experimental Infections Part I Hamster Infectionmentioning
confidence: 99%
“…Leptospirosis is tightly associated with inflammatory storms [8]. However, the therapeutic effect of immunosuppressant did not achieve the desired effect [9]. Combined with the gene expression profiles of golden hamsters and mice, we found that after infection with Leptospira, the gene expression of hamster's lags that of tolerant mice [10].…”
Section: Introductionmentioning
confidence: 91%
“…Thus the early inflammatory response is important to resist leptospirosis. That is why some immunosuppressive drugs, such as thalidomide and cyclosporine, fail to cure leptospirosis [8,9]. TLRs acting as pattern recognition receptors (PRRs) can recognize a variety of pathogen-associated molecular patterns (PAMPs) [10].…”
Section: Introductionmentioning
confidence: 99%